Chronic maxillary sinusitis: Clinical and microbiological evaluation - Shrestha, D; Yadav, LK; Thapa, P (Journal of College of Medical Sciences-Nepal, 2012)
Chronic sinusitis essentially results from untreated or inadequately treated acute sinusitis. Sinusitis is one of the common health problems worldwide. This is a prospective study, done in Department of ENT Bir Hospital Kathmandu. The study period was one year from 14 March 2009 to 15 March 2010. In this study the most commonly involved group is 21–30years (44%). The most presenting symptoms was Nasal discharge 46(92%) and nasal obstruction 44(88%). The most common sign was mucopus in nasal cavity in 44(88%) cases followed by post nasal drip in 39(78%) cases. The bacteria most frequently isolated from sinus aspirates were staphylococcus aureus 18(36%) and streptococcus pneumonia 16(32%). Majority of the aspirates 34(68%) cases yielded single organism. The antibiotic sensitivity testing showed that 48(96%) cases of isolates were sensitive to Cephalexin and ceftriaxone. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 17-22 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6675